2016
DOI: 10.1177/0003489416674962
|View full text |Cite
|
Sign up to set email alerts
|

The Utility of the MAUDE Database for Osseointegrated Auditory Implants

Abstract: The MAUDE database is limited in its design and given fairly disparate reporting quality may not be ideally suited for quantifying risks of OAIs. These findings suggest the necessity for a substantially improved central registry for otologic implants and highlight the need for further research to investigate the root causes of their associated complication.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 14 publications
0
18
0
Order By: Relevance
“…Though MAUDE contains a wealth of useful information, it lacks the proper mechanisms to allow for a clear systematic analysis . Since there is no required structure for events reporting, the reporting party can choose any format they please, leading to wide variability between reports that can lead to ambiguity regarding the nature of the adverse event.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Though MAUDE contains a wealth of useful information, it lacks the proper mechanisms to allow for a clear systematic analysis . Since there is no required structure for events reporting, the reporting party can choose any format they please, leading to wide variability between reports that can lead to ambiguity regarding the nature of the adverse event.…”
Section: Discussionmentioning
confidence: 99%
“…The MAUDE data base has been utilized to analyze adverse events in varied surgical subspecialties (8)(9)(10)(11)(12)(13). MAUDE studies are meant to identify serious complications that have occurred in practice, but may not be reported in the literature (9,14).…”
Section: Utility Of Maudementioning
confidence: 99%
“…The database has been used to examine a range of devices, including robot-assisted surgical systems, endometrial ablation devices, catheters, bone-anchored hearing aids, cochlear implants, among others. 11-15 We searched for all medical device reports between January 1, 2008, and January 1, 2019. Only 3 companies have sinus balloons that have been approved by the Food and Drug Administration: Entellus, Acclarent, and Medtronic.…”
Section: Methodsmentioning
confidence: 99%
“…In a recent study of the American College of Surgeons, it was found that only 12% of otolaryngologists had received claims against them in the past two years 1 , while a Danish study found an increasing trend in the number of otorhinolaryngology malpractice claims. In this specialty, complications are seldom severe, but are strongly surgery-related 2 , and, therefore, proper technical and non-technical skills and full compliance with guidelines and international standards are pivotal to avoid malpractice litigation 3 . "ENT Today" reported in October 2013 that, during the period 2007-2011, 53% of allegations against otolaryngologists were associated with "improper performance of surgery".…”
Section: Introductionmentioning
confidence: 99%
“…In this specialty, complications are seldom severe, but are strongly surgery-related 2 , and, therefore, proper technical and non-technical skills and full compliance with guidelines and international standards are pivotal to avoid malpractice litigation 3 . “ENT Today” reported in October 2013 that, during the period 2007-2011, 53% of allegations against otolaryngologists were associated with “improper performance of surgery”.…”
Section: Introductionmentioning
confidence: 99%